Analisis Ontologis, Epistemologis, dan Aksiologis dalam Ilmu dan Praktik Keperawatan Modern : Literature Review - Rifkal Artha Yuda; Dwina Oktavia Deli (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Modern nursing is often trapped in a technical-clinical routine, thus risking losing its basic essence as a scientific discipline. To maintain its professional identity, nursing requires a solid philosophical foundation through aspects of ontology, epistemology, and axiology. This study aims to synthesize the development of these three philosophical aspects in modern nursing practice, as well as identify their contributions to strengthening the nursing discipline. This study uses a narrative literature review design. Literature searches were conducted through the PubMed, ScienceDirect, and Google Scholar databases with keywords nursing philosophy, ontology, epistemology, axiology, and nursing science. Inclusion criteria included full-text articles in Indonesian and English published between 2016-2024 that specifically discuss the philosophy of nursing science. An analysis of ten selected articles shows that ontologically, nursing defines humans as holistic-relational entities. Epistemologically, there has been a shift from the dominance of positivism toward the integration of evidence-based science with intuitive and reflective knowledge. Axiologically, the value of caring remains the primary ethical compass. However, this study found a gap, where axiology and epistemology are often more dominant in educational curricula, while ontology (the essence of nursing's existence) tends to be neglected in bureaucratized clinical practice. The integration of nursing philosophy has proven crucial to preventing dehumanization in healthcare. The implications of this study's findings urge a reorientation of educational curricula and clinical practice standards that focus not only on technical competencies but also on strengthening philosophical foundations to ensure the sustainability of humanistic nursing science in the future.